Indonesian EFL Teacher’s Cognition on Written Corrective Feedback: a Case Study - Dayat (Journal of Edukasi Borneo, 2023)
Research on written corrective feedback (WCF) has extensively investigated student learning when receiving WCF, student engagement with teachers’ WCF, and perceptions of students and teachers to WCF. Yet, a handful of studies on WCF have explored the relationship between teacher knowledge and WCF practices. This study aimed to elaborate on an Indonesian academic writing teacher’s knowledge of WCF. A case study involving an experienced Indonesian academic writing teacher was employed. To gather data, a semi-structured interview was conducted. The findings indicated that the teacher’s knowledge of WCF was mediated by her language-learning experience. Thus, the teacher provided WCF on her students’ writing drafts by considering the students’ personalities and their level of writing ability. In correcting student writing errors, the teacher used several manners, direct and indirect correction, metalinguistic clues to the errors, and the reformulation of the wrong words. The relevant pedagogical implication was that the EFL teacher should also pay particular attention to providing WCF to improve the quality of academic writing. Abstrak Penelitian mengenai umpan balik korektif tertulis (WCF) telah menyelidiki secara ekstensif pembelajaran siswa ketika menerima WCF, keterlibatan siswa dengan WCF guru, dan persepsi siswa dan guru terhadap WCF. Namun, beberapa penelitian tentang WCF telah mengeksplorasi hubungan antara pengetahuan guru dan praktik WCF. Penelitian ini bertujuan untuk menguraikan pengetahuan guru penulisan akademik Indonesia tentang WCF. Sebuah studi kasus yang melibatkan seorang guru penulisan akademik Indonesia yang berpengalaman digunakan. Untuk mengumpulkan data, dilakukan wawancara semi terstruktur. Temuan menunjukkan bahwa pengetahuan guru tentang WCF dimediasi oleh pengalaman belajar bahasanya. Oleh karena itu, guru memberikan WCF pada rancangan tulisan siswanya dengan mempertimbangkan kepribadian siswa dan tingkat kemampuan menulisnya. Dalam mengoreksi kesalahan penulisan siswa, guru menggunakan beberapa cara, yaitu koreksi langsung dan tidak langsung, petunjuk metalinguistik terhadap kesalahan tersebut, dan perumusan ulang kata-kata yang salah. Implikasi pedagogis yang relevan adalah bahwa guru EFL juga harus memberikan perhatian khusus dalam menyediakan WCF untuk meningkatkan kualitas penulisan akademis. Kata Kunci: umpan balik tertulis, menulis akademis, bahasa Inggris sebagai bahasa asing